Determination of the structure and properties of an edge dislocation in rutile TiO2. (15th January 2019) - Maras, Emile; Saito, Mitsuhiro; Inoue, Kazutoshi; Jónsson, Hannes; Ikuhara, Yuichi; McKenna, Keith P.
Abstract: A global optimization procedure is used to predict the structure and electronic properties of the b  =  c [001] edge dislocation in rutile TiO2 . Over 1000 different atomic configurations have been generated using both semi-empirical and density functional theory estimates of the energy of the system to identify the most stable structure. Both stoichiometric and oxygen deficient dislocation core structures are predicted to be stable depending on the oxygen chemical potential. The latter is associated with Ti 3+ species in the dislocation core. The dislocation is predicted to act as a trap for electrons but not for holes suggesting they are not strong recombination centers. The predicted structures and properties are found to be consistent with experimental results obtained using scanning transmission electron microscopy and electron energy loss spectroscopy on samples produced using the bicrystal approach. Graphical abstract: Image 1